The Point Spread as a Reference Point: Evidence from the National Basketball Association - George Diemer; Michael Leeds (Journal of Applied Sports Management, 2022)
A contentious literature surrounds the claim that heavy favorites’ failure to cover the point-spread in National Collegiate Athletic Association (NCAA) basketball could indicate point-shaving. This paper extends the literature by using a new methodology to show that favorites in the National Basketball Association (NBA) also frequently fail to cover the spread. However, the high salaries in the NBA make point-shaving by players unlikely. Moreover, heavy underdogs also fail to cover the point spread and lose by more than expected. These seemingly anomalous findings are consistent with underdogs’ using the point-spread as a reference point.
Keywords: basketball; corruption; kernel density; NBA; reference points